Sodobni pogled na nastanek osteoporoze - Mencej Bedrač, Simona (Farmacevtski vestnik, 2012)
Two major problems related to osteoporosis are its high incidence and late diagnosis. It is predicted that the number of affected individuals will double till 2050. Recent findings have shown that osteoporosis develops as a consequence of imbalance in two key regulatory systems. RANKL/RANK/OPG system represents a crucial pathway involved in osteoclastogenesis, while Wnt signalling pathway plays a central role in osteoblastogenesis. In the recent years, numerous studies have shown the involvement of oxidative stress, immune system and inflammatory cytokines as well as adipogenesis in the pathogenesis of osteoporosis. The development of osteoporosis is influenced by several environmental and genetic factors. Many of them cannot be modified, but the incidence of osteoporosis can be markedly reduced by proper diet with sufficient amounts of calcium and vitamin D, regular physical activity and healthy lifestyle with no smoking and excessive use of alcohol.
Keywords: mehanizmi; osteoporoza; patologija